Publicly available data sources in sport-related concussion research: a caution for missing data - Abigail C. Bretzin; Bernadette A. D'Alonzo; Elsa R. van der Mei; Jason Gravel; Douglas J. Wiebe (BMC, 2024)
Abstract Background Researchers often use publicly available data sources to describe injuries occurring in professional athletes, developing and testing hypotheses regarding athletic-related injury. It is reasonable to question whether publicly available data sources accurately indicate athletic-related injuries resulting from professional sport participation. We compared sport-related concussion (SRC) clinical incidence using data from publicly available sources to a recent publication reporting SRC using electronic health records (EHR) from the National Football League (NFL). We hypothesize publicly available data sources will underrepresent SRC in the NFL. We obtained SRCs reported from two publicly available data sources (NFL.com, pro-football-reference.com) and data reported from the NFL's published EHR. We computed SRC per 100 unique player signings from 2015-2019 and compared the clinical incidence from publicly available data sources to EHR rates using clinical incidence ratios (CIR) and 95% confidence intervals (CI). Findings From 2015-2019, SRC counts from published EHR record data ranged from 135-192 during the regular season, whereas SRC counts ranged from 102-194 and 69-202 depending on the publicly available data source. In NFL.com the SRC clinical incidence was significantly and progressively lower in 2017 (CIR: 0.73, 95% CI: 0.58-0.91), 2018 (CIR: 0.66, 95% CI: 0.50-0.87), and 2019 (CIR: 0.48, 95% CI: 0.35-0.64) relative to the gold-standard EHR. In the pro-football-reference.com data, the documented SRCs in publicly available data sources for other years were ~ 20-30% lower than the gold-standard EHR numbers (CIRs 0.70-0.81). Conclusions Publicly available data for SRCs per 100 unique player signings did not match published data from the NFL's EHR and in several years were significantly lower. Researchers should use caution before using publicly available data sources for injury research.